Speakable me: the development of speech assistance tools for patients with speech disabilities - Abd Rahim, Noor Hayani; Abd Aziz, Nadia Natasha; Rosli, Nur Izyan; Hamid, Muhammad Hafizuddin (USIM Press, 2025)
This project involves analyzing and designing a system that functions as an Augmentative and Alternative Communication (AAC) to help individuals with speech and language disorders (e.g., aphasia and dysarthria) who are unable to use verbal speech to communicate by producing sounds based on the words entered by users. The main objective of this project is to assist patients with various types and levels of speech disabilities in communicating their needs, achieving a higher rate of Words Per Minute (WPM) with minimal financial cost. This system is developed using React Native, Visual Studio Code, and Firebase. Speakable Me provides three categories of speech assistants. In particular, Category 1 allows patients to enter the words with full spellings, and the system produces sounds based on the words entered. Meanwhile, Category 2 uses Morse code, which is a combination of 1 and 0 that has been pre-determined and assigned to a word in the library. This category aims to help patients with limited movement since it only requires patients to use two fingers to press the keys. Following this, Category 3 is a category that uses pictograms and has limited keys. Each key represents basic sentences and words that patients usually use. Patients need to press one key, and the system will voice out the whole sentence. Speakable Me also provides a feature that allows patients or their caregivers to add their own words and pre-recorded voices to the library for Categories 1 and 2. While sentences and words for Category 3 can be replaced, they are limited to the ten keys of the numbered keyboard